2018
DOI: 10.20473/amnt.v2i3.2018.254-264
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Usia, Stres, dan Asupan Zat Gizi Makro dengan Kejadian Obesitas Abdominal pada Ibu Rumah Tangga di Kelurahan Sidotopo, Surabaya

Abstract: Background: Abdominal obesity is one of the risk factors of cardiovascular diseases. Obesity is caused by energy imbalance. Women have higher risk of abdominal obesity than men. Objectives: This study aimed to analyze the association between age, stress level, macronutrient intake with abdominal obesity among housewives in Sidotopo, Surabaya. Method: This cross sectional study was conducted between May and July of 2018 in Kelurahan Sidotopo, Kecamatan Semampir, Kota Surabaya. The sample was 46 housewives aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 24 publications
1
4
0
6
Order By: Relevance
“…In this study, it was found that the number of respondents who were obese based on BMI measurements and waist circumference majorly were ≥ 40 years of age. This is in line with previous research which states that the risk of central obesity increases in accordance with someone's age as the prevalence of obesity as someone gets older 18 . As we get older, the metabolic processes in the body will decrease.…”
Section: Table 3 Distribution Of Body Mass Index Waist Circumferencsupporting
confidence: 92%
“…In this study, it was found that the number of respondents who were obese based on BMI measurements and waist circumference majorly were ≥ 40 years of age. This is in line with previous research which states that the risk of central obesity increases in accordance with someone's age as the prevalence of obesity as someone gets older 18 . As we get older, the metabolic processes in the body will decrease.…”
Section: Table 3 Distribution Of Body Mass Index Waist Circumferencsupporting
confidence: 92%
“…Individuals who experience stress due to unemployment or lack of work can engage in social activities and cope with stress management. One form of stress coping is watching television (36). In addition, creating activities that have economic value for the elderly can also be done in dealing with stress due to not working and feeling a burden on the family.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study indicated that there was a signifi cant relationship (p <0.05) between energy and fat intake and the percentage of visceral fat among foreign students at Universitas Airlangga, Surabaya. The intake of protein and carbohydrates with visceral fat in foreign students Nurrahmawati and Fatmaningrum (2018) where there was no signifi cant relationship between carbohydrate and protein intake with the incidence of central obesity.…”
Section: Relationship Between Macro Nutrient Intake and Viseral Fatmentioning
confidence: 94%
“…Table 1 shows that most of the respondents (52.3%) were young adults (18-25 years). Age has a signifi cant relationship with the incidence of central obesity (Nurrahmawati and Fatmaningrum, 2018). Most of the respondents (66.2%) are currently pursuing a Masters degree and the largest number of respondents are from postgraduate faculties.…”
Section: Respondents Characteristicmentioning
confidence: 99%